Optimize process parameter of FDM techniques to improve mechanical properties of aerospace application - Rathod, Himat; Makwan, Rishabh (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Fused Deposition modelling technique is widely accepted by industries as it is the one of the most convenient modern technology. The fused deposition modelling (FDM) is one of the additive manufacturing techniques which are largely used for printing of metal/thermoplastic materials with ease of design flexibilities the proposed research had been carried out for the investigation and optimization of process parameters for product or application development through FDM. The FDM- (Fused deposition Modelling) is widely used for product development and do contain various control variables. Here the process relates to nozzle temperature, base plate temperature, filament feed, filament material and deposition speed. The research presented here had been conducted considering nozzle temperature, layer thickness, and internal profile as variables for specimen manufacturing. In Aerospace application, optimization process is highly required for the Properties of material, weight and other effects. Hence the tensile specimen had been prepared to represent an aerospace application of ducts for airflow. The full factorial design of experiments had been considered for experimental investigation. The design of experiment had been conducted with three factors; three no. of parameters at three different levels Hence, A total no. of 27 representation samples had been prepared for tensile test and surface roughness for the Optimum result. The results had given considerable parametric effect as an outcome. The optimized results had been manufactured on an Ultimaker3D printer machine and tested which confirmed the results. The outcomes will assure optimal manufacturing process parameters of FDM for improved mechanical properties.